WEBSITE E-COMMERCE UNTUK PENJUALAN BAJU DI PASAR REMBANG (Information Technology and Telematics, 2015)
ABSTRACT The development of e-commerce easy to buy and order goods in webset, so do not need to come at the point of sale, however the development of website only have a positive impact, the negative effects also arise from the development of the website is selling shrimp now, access to the delivery still in doubtful for fraud in e-commerce website, This research will create an application that is able to secure payment transactions and delivery to consumers in order to satisfy, in the wake of this application by way of payment for transactions passing through emails, this application is designed receipts PHP which has been modified weeks to ordering and product selection. Keywords: e-commerce, sales, website